Assessment of soil erosion risks in response to land-use and land-cover changes in Coka watershed, Southern Ethiopia - Tadele Buraka; Eyasu Elias; Karuturi Venkata Suryabhagavan; Alemu Lelago (Geology, Ecology, and Landscapes, 2024)
ABSTRACTSoil erosion is a serious problem arising from agricultural intensification and other anthropogenic activities which can cause deterioration of soil fertility and productivity. This study aims to estimate total amounts of soil loss using the RUSLE and NDVI models and identify major areas of concern for management interventions through site specific in the Coka watershed, Southern Ethiopia. The RUSLE model required the integration of thematic factors such as rainfall, length and steepness of the slope, land-use and land-cover, soil erodibility, and control practices. These factors were calculated using remote sensing data and GIS. The results indicated that total area coverage from study of watershed under the degree of severity of erosion and priority was <5(very low), 5 − 10 (low), 10 − 18 (moderate), 18 − 50 (high), 50 − 100 (very high) and >100 t ha–1yr–1 (severe). Soil loss rates ranged between 2.33 in bare land and 237.16 t ha–1yr–1 in forest. Based on the findings, erosion risk having estimated soil loss (≥ 18 t ha–1yr–1) which is above tolerable range for the country containing 73% (2723 ha) from the total area coverage of watershed. Thus, appropriate soil and water conservation practices should be adopted to restore degraded lands and environment by giving attention for erosion hotspot areas.